Optimasi Biaya Distribusi Brownies Amanda Samarinda dengan Metode North West Corner dan Stepping Stone - Petrus Fendiyanto; Kurniawan Kurniawan (Universitas Cokroaminoto Palopo, 2025)
Efficient product distribution is one of the keys to the success of business operations, especially for culinary businesses with a wide sales network such as Brownies Amanda in Samarinda City. With two main outlets, which function as distribution centers, product delivery to several sales points in strategic locations requires optimal logistics cost planning. This study aims to determine a distribution scheme that minimizes the total shipping cost from two outlets located on Jalan Ahmad Yani and Jalan Bung Tomo to four sales points, namely on Jalan Wahid Hasyim, Jalan Slamet Riyadi, Jalan Bhayangkara, and Jalan Ampera (Palaran). The method used in this study is the classic approach in operations research, namely the North West Corner method to obtain an initial solution, which is then refined using the Stepping Stone method to achieve an optimal solution. Based on calculations and analysis, it was found that the optimal solution resulted in a total distribution cost of Rp 111.000, - with a shipping allocation that meets all demand and does not exceed the capacity of each outlet.